First-Year Ophthalmology Residency Call Structure and Its Association with Resident Anxiety and Confidence - McCoskey, Makayla; Shafer, Brian; Nti, Akosua; Ying, Gui-Shuang; Tapino, Paul; Pan, Wei; Addis, Victoria (Journal of Academic Ophthalmology, 2019)
Purpose The main purpose of this article is to characterize methods for preparing first-year ophthalmology residents for call and to evaluate the association between call structure and anxiety levels.Methods Data on call structure and preparatory courses were collected by a national online survey of residency program directors and first-year residents in 2016 and 2017. Anxiety was assessed using the Endler Multidimensional Anxiety Scale, and confidence in evaluating and managing critical diagnoses on call was evaluated using a modified Likert-type scale.Results In 2016, 132 first-year ophthalmology residents (28% of 465 total) responded to the survey, and in 2017, 103 first-year residents (22% of 469 total) responded, for a total of 235 residents participating. About 97.4% of residents reported that their residency program had a buddy call system, and 73.2% reported that their residency offered a preparatory course at the beginning of residency. In the resident cohort from 2017, there was a statistically significant association between length of buddy call duration and cognitive worry anxiety level (p = 0.01) with the lowest mean anxiety scores reported among those whose buddy call system lasted between 9 and 12 weeks. Higher confidence in making critical diagnoses on call was significantly associated with lower anxiety scores (p < 0.05 for all surveyed diagnoses). In the 2016 cohort, the mean cognitive worry score was significantly lower in those who had a preparatory course than those who did not (17.6 vs 22.2, p = 0.02), as was the mean overall anxiety score (33.8 vs 40.8, p = 0.04).Conclusion Buddy call and preparatory courses are associated with less anxiety and improved confidence among residents on call.
Keywords: residency; primary call; call structure; anxiety; confidence